2011
DOI: 10.1111/j.2041-1294.2011.00067.x
|View full text |Cite
|
Sign up to set email alerts
|

The Structural Role of Zn in Nuclear Waste Glasses

Abstract: Addition of ZnO and CaO to current United Kingdom high level nuclear waste (HLW) glass frits is currently under consideration with the aim of improving processing behavior and aqueous durability. This study was performed in order to better understand the structural role of Zn in model U.K. HLW glasses and, in particular, the role of Zn as a network modifier, intermediate, or former in such materials. Zinc K-edge X-ray absorption spectroscopy was applied to simple soda-lime-silicate glasses doped with ZnO and o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
27
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(29 citation statements)
references
References 23 publications
(47 reference statements)
2
27
0
Order By: Relevance
“…The second major peak corresponds to the O–O bond length at 2.61 Å. With the addition of ZnO, the PDF differs slightly: an additional Zn–O peak is observed at 1.96 Å, which compares favorably with the experimentally derived bond length of 1.95 Å observed for tetrahedral zinc in the same composition . Notably, the widths of the Si–O and O–O peaks remain unaltered.…”
Section: Resultssupporting
confidence: 60%
See 1 more Smart Citation
“…The second major peak corresponds to the O–O bond length at 2.61 Å. With the addition of ZnO, the PDF differs slightly: an additional Zn–O peak is observed at 1.96 Å, which compares favorably with the experimentally derived bond length of 1.95 Å observed for tetrahedral zinc in the same composition . Notably, the widths of the Si–O and O–O peaks remain unaltered.…”
Section: Resultssupporting
confidence: 60%
“…To combat this problem, it has been proposed to add zinc to the current glass composition. A number of experimental studies have shown that the addition of even small quantities of zinc oxide to the nuclear glass retards aqueous dissolution of both borosilicate and simpler silicate glass compositions . While many of the structural effects of zinc additions can be studied experimentally, no conclusive mechanism for the observed increase in glass durability has been identified.…”
Section: Introductionmentioning
confidence: 99%
“…Also, the electrostatic attraction of the excess of negative charge in the (ZnO 4 ) 2− tetrahedral should restrain further the mobility of Na + ions [41]. In general, zinc has been shown to exhibit a marked preference for square planar complexes in simple alkali silicate glasses [43] and therefore, in most cases of zinc-containing 45S5 BG, Zn 2+ can be a fourcoordinated weak network former [80]. Kapoor et al [44] studied the effect of zinc on the structure of melt-quenched alkali-free CaO-MgO-SiO 2 -P 2 O 5 -CaF 2 based glass system.…”
Section: Structure Physical and Mechanical Propertiesmentioning
confidence: 99%
“…B 2 O 3 is a glass forming oxide, TeO 2 is a conditional glass former, however, the structural role of zinc in such glasses is the subject of some controversy with evidence for behavior as a network former or a network modifier. Both Zachariasen and Warren's theory of glass structureand Dietzel's crystal field theory classify zinc as a network intermediate, i.e., able to adopt both network former and modifier roles depending upon glass matrix (Cassingham et al, 2010). Sm 2 O 3 is a modifier in the network, with these chemicals in the glass matrix, a low rate of crystallization, moisture resistant, stable and transparent glasses could be achieved.…”
Section: Erjmentioning
confidence: 99%